Molecular Characterization of Two Arabidopsis Ire1 Homologs, Endoplasmic Reticulum-Located Transmembrane Protein Kinases - Koizumi, Nozomu (American Society of Plant Physiologists, 2001)
A major response of eukaryotic cells to the presence of unfolded proteins in the lumen of the endoplasmic reticulum (ER) is to activate genes that encode ER-located molecular chaperones, such as the binding protein. This response, called the unfolded protein response, requires the transduction of a signal from the ER to the nucleus. In yeast (Saccharomyces cerevisiae) and mammalian cells, an ER-located transmembrane receptor protein kinase/ribonuclease called Ire1, with a sensor domain in the lumen of the ER, is the first component of this pathway. Here, we report the cloning and derived amino acid sequences of AtIre1-1 and AtIre1-2, two Arabidopsis homologs of Ire1. The two proteins are located in the perinuclear ER (based on heterologous expression of fusions with green fluorescent protein). The expression patterns of the two genes (using β-glucuronidase fusions) are nearly nonoverlapping. We also demonstrate functional complementation of the sensor domains of the two proteins in yeast and show that the Ire1-2 protein is capable of autotransphosphorylation. These and other findings are discussed in relation to the involvement of these genes in unfolded protein response signaling in plants.